Meningkatkan Hasil Belajar Peserta Didik Melalui Pembelajaran Berdiferensiasi Pada Materi Penyajian Data Di Kelas VII-H SMP Negeri 3 Surabaya Tahun Ajaran 2023/2024 - Nur Windyah Hasan; Suhartono Suhartono; Sunardi Sunardi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The research was carried out on the problem of the ability to understand mathematical material in the students of classes VII-H of the State 3 Surabaya High School. There are students who have the ability to understand material low, medium, and high. There are also students' learning needs that are not fulfilled so that they affect the learning outcomes of students. The aim of this study is to improve the learning outcomes of students through differential learning. The research uses the Class Action Research (PTK) method with a quantitative approach and data collection techniques using the results of individual student tasks. The results of the study using differential learning showed that the increased learning outcomes seen from pre-cycle activities were 18% up to 41% in the first cycle, then in the second cycle showed an increase with a percentage of 82%. From these results it can be concluded that the research using the differentiation learning was successful in improving the learning outcome of students of classes VII-H of the 3rd State Sub-secondary School of Surabaya at the point of mathematics lessons Data Presentation.